2019
DOI: 10.1136/bmjopen-2019-031317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family physicians on cervical cancer screening: cross-sectional questionnaire-based survey in a region of southern Poland

Abstract: BackgroundDespite worldwide efforts in encouraging routine pap smears for early detection of cervical cancer, Poland’s screening rate lags behind the rest of the European Union at 20.2%. Family physicians (FPs) in Poland rarely perform pap smears, and little is known about the experiences and attitudes of Polish patients regarding pap smear screening in a primary healthcare (PHC) setting.MethodsA cross-sectional questionnaire-based survey was performed. Questionnaires were distributed among 43 FPs and 418 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…While mammography, FOBT, and chest Xrays rarely became out-of-pocket expenses, almost 60% of thyroid ultrasounds and nearly half of smear tests were financed this way. Our results corroborate earlier findings that a large share-in some regions up to 50%-of all smear tests performed in Poland are financed out of pocket [50,57]. Additionally, in just the first half of 2018, as many as 13% of Polish adults paid for diagnostic tests out of pocket, mostly because of shorter waiting times in the private sector [58].…”
Section: Access To Servicessupporting
confidence: 90%
See 1 more Smart Citation
“…While mammography, FOBT, and chest Xrays rarely became out-of-pocket expenses, almost 60% of thyroid ultrasounds and nearly half of smear tests were financed this way. Our results corroborate earlier findings that a large share-in some regions up to 50%-of all smear tests performed in Poland are financed out of pocket [50,57]. Additionally, in just the first half of 2018, as many as 13% of Polish adults paid for diagnostic tests out of pocket, mostly because of shorter waiting times in the private sector [58].…”
Section: Access To Servicessupporting
confidence: 90%
“…For example among the female participants of our study, 75% had ever had a smear test, but only 74.3% of those had been given the test at least once every 3 years. The test could be performed in PHC offices and the acceptance for such practices among Polish patients was found to be high; unfortunately, it hardly ever happens in such settings [50]. Wielkopolskie in 2017-2018 was actually the only province in Poland with an increase in cervical cancer deaths in young women and with a relatively high death rate in the country [3].…”
Section: Participation In Secondary Preventionmentioning
confidence: 99%
“…On the other hand, the facilitating effects may be also explained by a specific service advantage that some members (general practitioners or specialized doctors) of the family doctor team usually undertake gynecological examination and cervical sampling procedures. A cross-sectional survey in Poland found that nearly two-thirds of patients were willing to undergo cervical cancer screening by their family doctors [ 32 ]. Therefore, FDCS may attract signing women to engage in screening behaviors as a result of operational accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a part of a survey performed among PHC doctors and their patients. Detailed information about the study design was published elsewhere [ 14 ].…”
Section: Methodsmentioning
confidence: 99%